Expression of exosomal microRNAs miR-34a and miR-210 in male infertility: relationship with morphokinetic parameters and sperm DNA fragmentation - Sh. N. Galimov; E. F. Galimova; I. R. Gilyazova; I. D. Gromenko; Yu. Yu. Gromenko; D. D. Gromenko; K. Sh. Galimov; V. D. Kotenko; T. Z. Tkeshelashvili; G. R. Abdeeva; P. F. Litvitsky; V. N. Pavlov (Вестник урологии, 2024)
Introduction. Infertility affects tens of millions of men and women across the globe. In approximately half of cases, male factors are the cause of infertility. In recent decades, there has been a significant decline in the quality of male ejaculate, which is characterized by reduced sperm concentration and motility. The insufficient diagnostic and prognostic value of routine semen analysis results highlights the challenge of developing effective diagnostic tools and searching for reliable biomarkers of male infertility. One of the most promising approaches may be assessing sperm microRNA expression.Objective. To study the role of sperm exosomal microRNAs miR-34a and miR-210 in the development of male infertility.Materials & methods. The retrospective study included 150 men aged 25 – 49 years; of these, 96 patients were diagnosed with idiopathic infertility. The comparison group consisted of 54 fertile men. To assess the structure and motility of sperm, the results of a standard ejaculate study (WHO, 2021) and computer data analysis using MMC Sperm (MMCSoft, St. Petersburg, Russia) software were used. The degree of DNA fragmentation was assessed using the TUNEL method. To analyze the expression of miR-34a and miR-210, quantitative real-time PCR was performed using the miRCURY LNA SYBR Green PCR Kit («Qiagen» GmbH, Hilden, Germany) and the Rotor-Gene Q PCR product detection system («Qiagen» GmbH, Hilden, Germany).Results. The study of ejaculate using the Computer Assisted Sperm Analysis System (CASA) method revealed a statistically significant relationship between the level of DNA fragmentation of sperm and indicators of the speed of their movement: rectilinear (VSL) (r = -0.522726; p < 0.01), curvilinear (VCL) (r = -0.499096; p < 0.01), along the middle path (VAP) (r = -0.429533; p < 0.01), as well as with the amplitude of lateral head displacement (ALH) (r = -0.294779, p < 0.01), the linearity of their curvilinear path (LIN) (r = -0.385796; p < 0.01), the degree of straight-line movements (STR) (r = -0.268248; p < 0.05) and their progressive mobility (r = -0.411547; p < 0.01). A study of the level of microRNA expression in sperm exosomes revealed a statistically significant decrease in its miRNA-34a pool (p = 0.0116). According to the Chaddock scale, the strength of the correlation between miR-210 expression and the effectiveness of ART programs was moderate (0.437993). The inverse relationship between miR-34a expression and IVF and ICSI results was weak (0.135314).Conclusion. The analysis of exosomal microRNA-34a and microRNA-210, which are involved in the regulation of spermatogenesis, reveals a direct correlation between their variations and changes in the kinetic and morphological parameters of gametes. It also indicates a relationship with the state of DNA fragmentation. These findings suggest varying levels of gene expression among infertile patients, men with proven fertility, and those undergoing assisted reproductive technology (ART) treatments, both with successful and repeated unsuccessful outcomes.